2000
DOI: 10.1177/146135570000200103
|View full text |Cite
|
Sign up to set email alerts
|

Victim—Offender Mediation and the Gatekeeping Role of Police

Abstract: This paper reports on implications for the management of police discretion arising from a Victim—Offender pilot project in Queensland, Australia. The pilot was conducted with juvenile offenders and was highly successful on a range of key outcomes related to restorative justice. However, the project suffered from very low referrals from police, and there were no referrals from the courts, partly because of magistrates' deference to police decisions. As a consequence, many crime victims and young offenders and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…On the other hand, it was identified that officers' decisions might vary according to their attitudes and opinions (Pollock, 1998;Reiner, 1996). This can lead to disparity and discrimination in the way people are processed (Cunneen, 2001;Prenzler & Hayes, 1999).…”
Section: Youth Justice Conferencing and Restorative Justicementioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, it was identified that officers' decisions might vary according to their attitudes and opinions (Pollock, 1998;Reiner, 1996). This can lead to disparity and discrimination in the way people are processed (Cunneen, 2001;Prenzler & Hayes, 1999).…”
Section: Youth Justice Conferencing and Restorative Justicementioning
confidence: 98%
“…These reasons included officers' lack of awareness of the availability of conferencing, lack of training in the necessary administration procedures, and the inability to attend conferences due to operational constraints. While these explanations all revolve around operational issues, a competing explanation for officers' reluctance to refer to a conference is the inappropriate use of their discretionary powers (Prenzler & Hayes, 1999). The purpose of this research was to investigate the reasons for the low rate of referrals by examining police attitudes towards conferencing and their use of discretion.…”
Section: Introductionmentioning
confidence: 99%
“…That is, while police are not sole determinants of individual outcomes and have very limited discretion where serious (e.g. violent) crime has occurred, they are nevertheless the key entry point or ‘gatekeepers’ to the justice and diversionary systems (Prenzler & Hayes, 2000; Schulenberg & Warren, 2009; Stewart & Smith, 2004). The following section explores the literature on police discretionary decision-making.…”
Section: Introductionmentioning
confidence: 99%